2020
DOI: 10.1371/journal.pbio.3000908
|View full text |Cite
|
Sign up to set email alerts
|

Modeling flexible behavior in childhood to adulthood shows age-dependent learning mechanisms and less optimal learning in autism in each age group

Abstract: Flexible behavior is critical for everyday decision-making and has been implicated in restricted, repetitive behaviors (RRB) in autism spectrum disorder (ASD). However, how flexible behavior changes developmentally in ASD remains largely unknown. Here, we used a developmental approach and examined flexible behavior on a probabilistic reversal learning task in 572 children, adolescents, and adults (ASD N = 321; typical development [TD] N = 251). Using computational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 91 publications
(116 reference statements)
2
45
0
Order By: Relevance
“…Our finding of both decreasing preference uncertainty and increasing model fit with age reflect that behaviour is less variable in older subjects within our sample. Varying goodness-offit of a specific model is a challenge for developmental modelling studies 61,62 and may be indicative of either varying stochasticity or different cognitive processes underlying task behaviour at different ages. Potential solutions are now emerging in the literature, including novel data analysis strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of both decreasing preference uncertainty and increasing model fit with age reflect that behaviour is less variable in older subjects within our sample. Varying goodness-offit of a specific model is a challenge for developmental modelling studies 61,62 and may be indicative of either varying stochasticity or different cognitive processes underlying task behaviour at different ages. Potential solutions are now emerging in the literature, including novel data analysis strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In another associative learning study where adults had to learn an association between a tone and a rotation direction in a very uncertain context, autistic adults managed to learn a prior, but failed to update it after an unexpected change in contingency [ 26 ]. Another study relying on a large cohort of children and adults performing a probabilistic reversal learning task also showed poorer performance in ASD and reduced flexible behaviours [ 27 ]. Finally, another probabilistic reward learning task in a volatile environment showed that having more autistic traits was associated with worse performance [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the enhanced novel discrimination learning, reversal learning was impaired in Nrxn1α +/− mice. This has translational relevance to the reversal learning deficit seen in neurodevelopmental disorders associated with 2p16.3 deletion, including that in ASD (Crawley et al, 2020), ScZ (Reddy et al, 2016; Schlagenhauf et al, 2014), and TS (Shephard et al, 2016). However, while these studies generally indicate perseveration and/or a lack of sensitivity to feedback as key mechanisms in the reversal learning deficit seen in these disorders (Crawley et al, 2020; Reddy et al, 2016), we found that sensitivity to punishment/feedback was not impaired in Nrxn1α +/− mice.…”
Section: Discussionmentioning
confidence: 98%
“…Despite these observations in relatively simple tests, the potential impact of Nrxn1α heterozygosity on discrimination/associative learning and cognitive flexibility has not been assessed. This is surprising given the altered discrimination learning (Plaisted et al, 1998), associative learning (Brambilla et al, 2011; Eordegh et al, 2020) and cognitive flexibility, including impaired reversal learning (Crawley et al, 2020; Lange et al, 2017; Schlagenhauf et al, 2014), reported in neurodevelopmental disorders associated with 2p16.3 deletion.…”
Section: Introductionmentioning
confidence: 99%